Stopping exploitation: properly remunerating healthcare workers for risk in COVID-19 pandemic - Giubilini, A; Savulescu, J (Wiley, 2021)
We argue that we should provide extra payment not only for extra time worked but also for the extra risks healthcare workers (and those working in healthcare settings) incur while caring for COVID-19 patients – and more generally when caring for patients poses them at significantly higher risks than normal. We argue that the extra payment is warranted regardless of whether healthcare workers have a professional obligation to provide such risky healthcare. Payment for risk would meet four essential ethical requirements. First, assuming healthcare workers do not have a professional obligation to take on themselves the risks, payments in the form of incentives would preserve autonomy in deciding what risks to take on oneself. Second, even assuming that healthcare workers do have a professional obligation to take on themselves the risks, payments for risk would create fair working conditions by avoiding exploitation. Third, payments for risk would make it more likely that public healthcare systems can discharge their institutional responsibility to provide healthcare in circumstances where healthcare workers may otherwise legitimately opt out. Fourth, payments for risk would guarantee an efficient healthcare system in pandemic situations. Finally, we address two likely objections that some would raise against our proposal, particularly with regard to incentives, namely that such payments or incentives can themselves be coercive and that they represent a form of undue inducement.